The Effectiveness of Jigsaw Technique in Teaching Reading at The Second Grades Student of Senior High School - Rosyidi, Ahmad Zuhri; Hadi, M. Wahyu (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The purpose of this research is to find out the effectiveness of Jigsaw technique in teaching reading. This study used an experimental design. The population of the research was 29 students and the sample was taken 29 students from all of the population. To take the sample the present researcher used purposive sampling technique. In collecting data, the present researcher used instrument to measure students’ effectiveness of Jigsaw Technique in reading. To analyze data, the present researcher used paired-samples t-test to find out the effectiveness of the technique. The result of data analysis that there was a significant difference in the scores between the pre-test and the post-test, was significance at p = 0.000, meaning that the null hypothesis is rejected (Ho) and alternative hypothesis is accepted (Ha).It means that there was a significant effectiveness of Jigsaw Technique in teaching reading for the tenth graders of MA NW Sikur in the academic year 2023-2024.